Multi-study feasibility analysis on a composite biomarker of inflammatory resilience to quantify the effects of energy restriction on low-grade inflammation in overweight and obese individuals. - Dessing, Mark C.; van den Broek, Tim J.; Hoevenaars, Femke P. M.; van den Brink, Willem J.; Rundle, Milena; Frost, Gary; Afman, Lydia; Wopereis, Suzan (European Journal of Nutrition, 2025)
Purpose: Assessing the health impacts of nutritional interventions in metabolically compromised but otherwise healthy individuals is challenging, necessitating sensitive tools. Phenotypic flexibility offers an innovative way to measure homeostatic capacity during challenge tests. A composite biomarker of inflammatory resilience has proven useful in evaluating the health benefits of whole-grain wheat interventions in overweight and obese individuals. Expanding this method to other dietary interventions to combat low-grade inflammation is essential. Methods: This study investigated the feasibility of a composite biomarker of inflammatory resilience through secondary analysis of samples from two independent energy restriction (ER) trials, Bellyfat (NCT02194504) and Nutritech (NCT01684917). In these trials, fasting and postprandial inflammation was analysed using a variety of markers. Four composite biomarker models were developed on the basis of postprandial inflammatory marker responses via the 'health space' model method. These models were statistically evaluated for their sensitivity in detecting the effects of 12 weeks of ER. Results: The minimal composite biomarkers, consisting of IL-6, IL-8, IL-10, and TNF-α, lacked the ability to detect postprandial intervention effects in both ER trials. However, in the Nutritech study, the extended, endothelial, and optimized composite biomarkers of inflammatory resilience displayed significant responses to the ER (all P < 0.005). In the latter 3 models, a reduction in the inflammatory score was correlated with a reduction in BMI and body fat percentage. Conclusion: This study underscores the feasibility of employing a composite biomarker of inflammatory resilience to evaluate ER interventions. Further validation in additional nutritional intervention studies is necessary. Once validated, this composite biomarker could offer a novel approach for assessing low-grade inflammation and phenotypic flexibility.